"To Catch or Not to Catch": Microcapsule‐Based Sandwich Assay for Detection of Proteins and Nucleic Acids. (16th June 2016) - Verma, Sujit K.; Amoah, Amanda; Schellhaas, Ulla; Winterhalter, Mathias; Springer, Sebastian; Kolesnikova, Tatiana A.
Abstract : The development of new assays that specifically detect intermediate or final products of biotechnological processes or multiple analytes in biomedical research is important for diagnostics and biotechnology. This study presents a microcapsule‐based sandwich assay for detection of proteins and nucleic acids using flow cytometry as an optical readout. The main component of the assay are robust chemically cross‐linked microcapsules that are coated with adaptor proteins such as protein A or streptavidin. In the first approach, the ability of detecting the blood cancer biomarker beta‐2 microglobulin in the fM to pM concentration range with the help of protein A‐coated capsules is demonstrated. In the second approach, streptavidin‐coated capsules are used for detection of nucleic acids in the nM concentration range. The developed assay allows rapid quantitative analyte measurement, while providing high sensitivity and selectivity at very small sample quantities. In the future, protein A‐ and streptavidin‐coated microcapsules can be used as universal tools for detection of a broad range of analytes. Abstract : The development of a microcapsule‐based assay for detection of proteins and nucleic acids using flow cytometry as an optical readout is described. (PAH/PAA)2 capsules are chemically cross‐linked and coated with protein A or streptavidin, which allow capturing antibodies or biotinylated molecules in optimized orientation. The detection is performed on the capsule surface, when the analyte is sandwiched between a binder and a detector molecule. The assay sensitivity and selectivity are verified using the biomarker protein human beta‐2 microglobulin and small oligonucleotide molecules as analytes.